Congenital Hydrocephalus in a Calf and its Surgical Treatment: A Case Report - Saini, R; Sharma, SK; Aziz, PR; Mir, LA; Pooniya, R (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Hydrocephalus is an accumulation of excessive fluid in durameter or ventricles of the brain (Purohit et al., 2012) thereby leading to the swelling of the cranium. It is mainly due to abnormal development of the fetus during pregnancy; however, hereditary, infectious, and nutritional factors can also predispose this condition.